Analysis of Workers’ Unsafe Actions Using a Behavior-Based Safety (BBS) Approach to Improve Occupational Safety at CV. Adhi Putra Bantul - Fikri Raika Akbar; Hasti Hasanati Marfuah (Institut Teknologi Dirgantara Adisutjipto, 2026)
Construction projects are among the industrial sectors with a high risk of work accidents due to unsafe working behavior and dynamic working conditions. This study aims to analyze workers’ unsafe actions using a Behavior-Based Safety (BBS) approach to improve occupational safety at CV. Adhi Putra Bantul. Data were collected through direct observation, interviews, and documentation during fieldwork activities on a two-story house construction project. The results showed several dominant unsafe actions, including not using personal protective equipment (PPE), working at heights without safety protection, manual material handling up and down stairs, and non-ergonomic working postures. Based on the risk analysis, not using PPE and working at heights without protection were categorized as high-risk behaviors. The BBS analysis indicated that unsafe actions occurred repeatedly due to the lack of safety intervention systems, limited supervision, and the absence of a structured safety culture. Therefore, several recommendations were proposed, including implementing daily safety briefings, requiring PPE, improving work ergonomics, and applying behavior-based observation checklists. The implementation of these recommendations is expected to reduce unsafe actions and improve occupational safety in construction projects.